2016
DOI: 10.1016/j.jeurceramsoc.2015.09.022
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrofluoric acid etching of dental zirconia. Part 2: effect on flexural strength and ageing behavior

Abstract: Among the diverse treatments proposed to promote the osseointegration of zirconia dental implants, hydrofluoric acid (HF) etching appears to be a good candidate. However little is known on the effect of this process on the mechanical properties and long-term reliability. In this work, the surface integrity, the flexural strength and the ageing sensitivity of yttria-stabilized zirconia were assessed after etching in HF 40%. Results show that etching induces an increase of monoclinic phase content and a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…This indicates that although the average roughness, the surface material volume and the surface core void volume do not increase substantially after one hour, localized events such as etching pits likely become bigger. This was confirmed by topographical images ( Figure 7) and is not desirable from the mechanical point of view since those localized events could act as defects originating fracture [18]. On the other hand, it has to be noticed that for the functional indexes S bi , S ci and S vi the transition seems to happen around thirty minutes.…”
Section: Evolution Of the Surface Topography Over Etching Timementioning
confidence: 71%
See 1 more Smart Citation
“…This indicates that although the average roughness, the surface material volume and the surface core void volume do not increase substantially after one hour, localized events such as etching pits likely become bigger. This was confirmed by topographical images ( Figure 7) and is not desirable from the mechanical point of view since those localized events could act as defects originating fracture [18]. On the other hand, it has to be noticed that for the functional indexes S bi , S ci and S vi the transition seems to happen around thirty minutes.…”
Section: Evolution Of the Surface Topography Over Etching Timementioning
confidence: 71%
“…The objectives of the present work are therefore to determine suitable conditions for a fast and uniform roughening of dental zirconia, to provide a complete surface characterization with a special emphasis on topography and to contribute to the understanding of the etching mechanism. Questions related to the influence of etching on the mechanical properties and long-term reliability are treated in a second article [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these topographical changes, previous works showed that HF etching induces an increase in the fluorine content of the surface 31 and the formation of a superficial submicrometric porosity. 32 Nevertheless, these surface alterations were shown to be nearly independent from etching time. Surface structural and chemical changes along the gradients can thus be considered as negligible.…”
Section: Discussionmentioning
confidence: 98%
“…As shown in Figure , the samples were immersed into a volume of 40 mL of HF contained in a polyethylene flask at a speed of 0.6 mm/min by using an automated device (ND‐R Rotary Dip Coater, Nadetech Innovations, Spain). The total duration of the process was set to 1 h, which leads to a substantial roughness for the part of the sample immersed for the longest time without damaging too severely the material . After etching, the specimens were rinsed with deionized water in order to stop the reaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation